1985
DOI: 10.3109/00207458508985369
|View full text |Cite
|
Sign up to set email alerts
|

Directional Preferences in Perception of Visual Stimuli

Abstract: The present paper reviews a series of studies regarding the effects of hemispheric asymmetry and reading and writing habits on directional preferences in reproducing horizontally-displayed visual stimuli. Hebrew readers, English readers, and Arabic readers were presented with arrays of horizontally-displayed directional and nondirectional stimuli, as well as with single stimuli. They were asked to reproduce the stimuli, and the direction of their reproduction, left-right or right-left, was recorded for analysi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
31
0

Year Published

1988
1988
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(35 citation statements)
references
References 56 publications
4
31
0
Order By: Relevance
“…In a first step, data transformation from Brain Vision Analyser to sLORETA software was performed, using a protocol by Mückschel et al [45]. Using the sLORETA software, we then performed voxel-wise randomisation tests with 5000 permutations, based on statistical non-parametric mapping (SnPM).…”
Section: Sloretamentioning
confidence: 99%
“…In a first step, data transformation from Brain Vision Analyser to sLORETA software was performed, using a protocol by Mückschel et al [45]. Using the sLORETA software, we then performed voxel-wise randomisation tests with 5000 permutations, based on statistical non-parametric mapping (SnPM).…”
Section: Sloretamentioning
confidence: 99%
“…Temporal order of events is gestured left to right in native Spanish speakers but right to left in native Arabic speakers, even when speaking Spanish (e.g., Santiago, Lupiáñez, Pérez, & Funes, 2007). Writing order affects perception of motion (e.g., Maass, Pagani, & Berta, 2007;Morikawa & McBeath, 1992), perceptual exploration and drawing (e.g., Chokron & De Agostini, 2000;Nachshon, 1985;Vaid, Singh, Sakhuja, & Gupta, 2002), aesthetic judgments (e.g., Chokron & De Agostini, 2000;Nachshon, Argaman, & Luria, 1999), emotion judgments (Sakhuja, Gupta, Singh, and Vaid, 1996), judgments of agency, power, and speed (Chatterjee, 2001(Chatterjee, , 2002Hegarty, Lemieux, & McQueen, in press;Maass & Russo, 2003;Suitner & Maass, 2007), and art (Chatterjee, 2001;McManus & Humphrey, 1973). A variety of factors correlated with reading order seem to underlie these effects.…”
Section: Direction In Space: Horizontalmentioning
confidence: 99%
“…However, cross-cultural research has often found total, or at least partial, reversals in cultures where languages are written from right to left (RL), such as Arabic, Hebrew, or Urdu, suggesting that language-related scanning habits play an important role in such spatial asymmetries. Indeed, reversals have been reported in many different areas of psychology and on different tasks, including inhibition of return (Spalek & Hammad, 2004), representational momentum (McBeath, Morikava, & Kaiser, 1992), imaginary number line (Dehaene, Bossini, & Giraux, 1993), visual imaging of subject-verb-object sentences (Maass & Russo, 2003), and drawing, exploration of art, and aesthetic preferences (e.g., Chokron & De Agostini, 2000;Nachshon, 1985;Nachshon, Argaman, & Luria, 1999;Tversky, Kugelmass, & Winter, 1991). Some studies also suggest that culture-specific asymmetries in space perception and directional tendencies only occur after learning to read and to write, as in the case of Fagard and Dahamen's (2003) study comparing French and Tunisian children, suggesting that writing/reading habits are implicated in spatial bias.…”
Section: Theoretical Explanations Of Spatial Asymmetriesmentioning
confidence: 99%